Electronic Media Device Usage and Its Associations With BMI and Obesity in a Rapidly Developing City in South China - Qiu, Ying; Xie, Yao Jie; Chen, Liping; Wang, Shao Ling; Yang, Hualu; Huang, Zhenzhen; Liu, Ping; Mo, Beirong (Frontiers in Public Health, 2021)
Objective: This study aimed to evaluate the television (TV) viewing and computer and mobile phone usage duration in a community sample of Chinese adults and examine their associations with BMI and obesity. Methods: We conducted a community-based health needs assessment study from February to December 2018 among 2,873 Chinese adults in Nanshan District of Shenzhen, China. We used self-administered questionnaires to collect the data from 24 community health service centers in Nanshan District. The participants individually recorded the time they spent watching TV and using computers and mobile phones. They also answered questions about their sociodemographic and lifestyle factors. We measured their height and weight by using ultrasonic height and weight scales. Then, we calculated and categorized their BMI in accordance with the standards prescribed by the World Health Organization for Asians. Results: Most of the participants were young adults (aged 18–44 years, 74.2%). The overall prevalence of obesity was 15.30%. The prevalence of TV, computer, and mobile phone usage was 75.5, 71.2, and 93.8% in females and 71.1, 75.7, and 94.2% in males, respectively. The youth (18–24 years) and the elderly (65 years or older) had the longest time using mobile phones (3.78 ± 2.51 h) and watching TV programs (2.12 ± 1.38 h), respectively. Longer usage of computers and mobile phones was evident in males (p < 0.05) and participants with a high education level (p < 0.01). The univariate analysis results showed an association between high BMI and obesity and short duration of using computers and mobile phones (all p < 0.05). By contrast, no significant associations were found between the length of TV program viewing and mobile phone usage and BMI (p > 0.05). After we adjusted for potential confounders, we found that computer usage time and the overall usage time of the three electronic devices had an inverse association with BMI (p < 0.05). Conclusions: Mobile phones were the most popular electronic device in Nanshan residents of Shenzhen. Unlike most previous studies, we found an inverse association between screen time and BMI. Nevertheless, scholars should conduct further studies to explore this association. Overall, we strongly encourage the appropriate use of electronic devices.